2012
DOI: 10.1016/j.jacc.2012.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence, Awareness, Management, and Control of Hypertension Among United States Adults, 1999 to 2010

Abstract: From 1999 to 2010, prevalence of hypertension remained stable. Hypertension awareness, management, and control were improved, but remained poor; nevertheless, there has been no improvement since 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
277
7
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 361 publications
(319 citation statements)
references
References 25 publications
28
277
7
7
Order By: Relevance
“…The higher incidence of hypertension in blacks compared with whites in the current study is consistent with previous cross‐sectional and longitudinal studies 3, 4, 5, 6, 7, 8, 15, 16. In a previous analysis of the CARDIA study, 10‐year incidence of hypertension was 16.4% in black men, 13.1% in black women, 7.8% in white men, and 3.2% in white women 3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher incidence of hypertension in blacks compared with whites in the current study is consistent with previous cross‐sectional and longitudinal studies 3, 4, 5, 6, 7, 8, 15, 16. In a previous analysis of the CARDIA study, 10‐year incidence of hypertension was 16.4% in black men, 13.1% in black women, 7.8% in white men, and 3.2% in white women 3.…”
Section: Discussionsupporting
confidence: 92%
“…Cross‐sectional studies using data from the National Health and Nutrition Examination Survey (NHANES) have consistently reported a higher prevalence of hypertension in blacks compared with whites beginning at a young age 4, 5, 6, 7, 8. However, few studies have used longitudinal data to quantify the cumulative incidence of hypertension from young adulthood through middle age among blacks and whites.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are need to unravel the underlying causes of this troubling phenomena. The improvements in mean blood pressure and blood cholesterol may reflect the healthy trends in the US population, including decreases in the proportion of dietary saturated fat; increases in fruits and vegetables and the proportion of polyunsaturated and monounsaturated fats in the diet34, 35, 36, 37; decreased smoking38, 39, 40; and increased awareness, identification, and pharmacological treatment of high cholesterol and blood pressure levels 25, 41…”
Section: Discussionmentioning
confidence: 99%
“…Babatsikou and Zavitsanou (2010) reported that the prevalence of HTN in European and American elderly populations ranges from 53% to 72% (35). The prevalence of HTN in elderly individuals was 66.7% in the United States (36), and 58% in Belarus (37). (11).…”
Section: Discussionmentioning
confidence: 99%